Administrative, institutional and political control of the budget - theoretical aspect with a brief review of some positive legal solutions of Serbia - Milić, Stefan (Glasnik Advokatske komore Vojvodine, 2023)
The modern state has a significant role in providing public goods in order to make their use possible for all its inhabitants. The state must provide certain revenues in order to be able to perform this function. The institution that best reflects how the state manages its economy and directs its revenues is the budget. Bearing in mind that the budget shows in detail the financial plans for a certain next period, the procedure of adopting and controlling the budget is very important. In order to ensure that the revenues that the state financially manages are directed in a way that would benefit the citizens the most, there must be an effective mechanism for controlling the adoption and implementation of the budget. Budget control can be carried out by administrative bodies, independent bodies and parliament as the body that adopts the budget and the final budget account. Thus, the subject of this paper’s analysis will be administrative, institutional and political control of the budget. With these three types of control, the author will briefly refer to some positive legal solutions in Serbia. Administrative control is based on a hierarchical principle, institutional control is performed by independent audit institutions, while political control is performed by the parliament as the highest representative body.